2003
DOI: 10.1136/vr.153.12.347
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of faecal excretion of verocytotoxigenic Escherichia coli 0157 in cattle in England and Wales

Abstract: During the decade to 1999, the incidence of human infections with the zoonotic pathogen verocytotoxin-producing Escherichia coli O157 (VTEC O157) increased in England and Wales. This paper describes the results of a survey of 75 farms to determine the prevalence of faecal excretion of VTEC O157 by cattle, its primary reservoir host, in England and Wales. Faecal samples were collected from 4663 cattle between June and December 1999. The prevalence of excretion by individual cattle was 4.2 per cent (95 per cent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 35 publications
13
63
1
2
Order By: Relevance
“…The prevalence estimate for England & Wales is substantially lower than those reported previously [13,14]. Possible reasons for this include differences in how previous surveys defined an eligible farm, their sampling approach, the distribution of herds across management types and their seasonal distribution of sampling.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The prevalence estimate for England & Wales is substantially lower than those reported previously [13,14]. Possible reasons for this include differences in how previous surveys defined an eligible farm, their sampling approach, the distribution of herds across management types and their seasonal distribution of sampling.…”
Section: Discussionmentioning
confidence: 71%
“…Sample sizes were estimated using reported prevalence from previous surveys (Scotland 20·5% [12] and England & Wales 39% [13]). Based on the proportion of herds positive and a sensitivity of 90%, sampling at least 110 farms in Scotland and 160 farms in England & Wales would provide 96% confidence that the true herd-level prevalence of E. coli O157 would fall within a tolerance range of 0·169 of the apparent prevalence estimated in these surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 156 farms were excluded due to ineligibility. Sample sizes were calculated by a multilevel approach with design-effects and intra-class correlations deducted from variance between pats, groups and farms observed in a previous field study on a similar population [13]. The required samples sizes were 48 control farms and 48 farms in each intervention group to detect a risk ratio of 5 at 80% power with 95% confidence, when using a design effect of 13.2 2 to adjust for a group cluster size of 20 pat samples per group per visit.…”
Section: Methodsmentioning
confidence: 99%
“…Young cattle between 2-18 months of age are at highest risk of excreting E. coli O157 through faeces or saliva [13]. Shedding by the individual animal is intermittent, probably due to re-circulation of the pathogens between animals or the environment and recent simulation models have suggested that the majority of transmission occurs through the environment, especially when young-stock are housed [10].…”
Section: Introductionmentioning
confidence: 99%